Dynamics of Indirect Land-Use Change: Empirical Evidence from Brazil - Saraly Andrade de Sá; Charles Palmer; Salvatore Di Falco (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
The expansion of a given land use may affect deforestation directly if forests are cleared to free land for this use, or indirectly, via the displacement of other land-use activities from non-forest areas towards the forest frontier. Unlike direct land conversion, indirect land-use changes affecting deforestation are not immediately observable. They require the linking of changes occurring in different regions. This paper empirically assesses the possible indirect effects of sugarcane expansion in Brazil's state of S\~ao Paulo, on forest conversion decisions in the country's Amazon region. Further, it examines the evidence for a mechanism through which these effects might materialize, namely a displacement of cattle ranching activities from S\~ao Paulo state to the Amazon. The results suggest a positive relationship between sugarcane expansion and deforestation. This indirect land-use effect is shown to be a dynamic process materializing over 10 to 15 years.
Keywords: Q15; Q24; Q42; 330; Indirect land-use changes; Dynamic effects; Biofuels; Deforestation; Entwaldung; Agrarboden; Biokraftstoff; Zuckeranbau; Brasilien